Dampak Sosial Penerapan Pembelajaran Full Day School di MTs Swasta Ummi Lubuk Pakam - Putri Winanda; Sakti Ritonga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the social impact of implementing Full Day School learning. The purpose of this study is to describe the social impact of implementing Full Day School learning at Mts Swasta Ummi Lubuk Pakam. This study uses a qualitative approach. The research method applied is descriptive analytical using data collection techniques through observation, interviews, and documentation. The findings show that the implementation of the Full Day School system at MTs Swasta Ummi Lubuk Pakam has a complex social impact on students. On the one hand, this system has succeeded in improving social skills and character development. However, on the other hand, it can have negative impacts, namely fatigue and stress, reduced interaction with family, and decreased involvement in neighborhood activities. To overcome this, the school designs a comprehensive strategy by paying attention to the balance of academic and emotional needs of students. Providing sufficient rest time, building character and soft skills development programs, establishing cooperation with parents and the community, and humanistic counseling services are part of the holistic approach applied. Through this strategy, the school seeks to create a healthy, inclusive learning environment that supports the overall development of students.